2022
DOI: 10.21037/apm-22-708
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in gynecologic oncology: a narrative review of current literature and vision for the future

Abstract: Background and Objective: Several professional societies have recommended incorporating palliative care into routine oncology care, yet palliative care remains underutilized among women with gynecologic cancers. This narrative review highlights current evidence regarding utilization of palliative care in gynecologic oncology care. Additionally, the authors offer recommendations to increase early integration and utilization of palliative care services, improve education for current and future gynecologic oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A prior systematic review in 2016 revealed at least twenty published criteria assessing six functional domains (25). This includes multiple sets of "consensus criteria" introduced by NCCN, Center to Advance Palliative Care (CAPC), and an International Delphi consensus with further studies performed with adapted or modified versions of the consensus criteria (13,25). Similarly, multiple patient symptom screening instruments exist through ESAS-r and the Patient Reported Outcomes Measurement Information System (PROMIS ® ) (22,23).…”
Section: Reassessing Screening Methods From An Implementation Science...mentioning
confidence: 99%
See 3 more Smart Citations
“…A prior systematic review in 2016 revealed at least twenty published criteria assessing six functional domains (25). This includes multiple sets of "consensus criteria" introduced by NCCN, Center to Advance Palliative Care (CAPC), and an International Delphi consensus with further studies performed with adapted or modified versions of the consensus criteria (13,25). Similarly, multiple patient symptom screening instruments exist through ESAS-r and the Patient Reported Outcomes Measurement Information System (PROMIS ® ) (22,23).…”
Section: Reassessing Screening Methods From An Implementation Science...mentioning
confidence: 99%
“…Identified screening methods underperformed in terms of increasing palliative care utilization across the spectrum of practice settings. Salyer et al (2022) proposed that palliative care will be implemented through one of three models based on whether a given institution has access to (I) primary palliative care only, (II) primary palliative care + inpatient specialty palliative care only, or (III) primary palliative care + inpatient and outpatient specialty palliative care (13). Hui et al (2022) similarly suggested that given the scarcity of palliative care resources, screening should move beyond solving for early palliative care referral (i.e., how can we identify the entire universe patients who may benefit from integrated palliative care and get them evaluated by palliative care as expediently as possible?)…”
Section: Operationalizing Palliative Care Delivery: Toward a Personal...mentioning
confidence: 99%
See 2 more Smart Citations
“…They suggest guidelines for when to refer to palliative care, tailored to settings with varied access to palliative care consultations as inpatient, outpatient or both. They also introduce "primary palliative care", which are aspects of palliative care that they argue gynecologic oncologists should be expected to provide; for example, basic management of nausea, constipation, and goals of care conversations (3). They also focus on ways that this training can be achieved.…”
mentioning
confidence: 99%